The Influence of Campaign Style on Political Participation of Lampung Community in Regional Head Elections - Abdul Halim; Agus Rizki Alfalah; Aisyah Suci Ningrum; Anggita Aprilia; Virda Septiani (Penerbit Hellow Pustaka, 2025)
Community political participation is an important indicator in assessing the quality of democracy, especially in the context of regional head elections (Pilkada). Various campaign strategies have been implemented by regional head candidates to increase voter participation. This study aims to analyze the influence of campaign style on the level of community political participation in Lampung Province. The method used is a descriptive quantitative approach by distributing questionnaires to 60 respondents from various groups. The results of the study indicate that a campaign style involving direct interaction, the use of social media, and an inclusive approach has a positive influence on political participation. This finding emphasizes the importance of innovation in campaign strategies to reach all levels of society, including young voters and women.